Decreased Implant Survival is Associated With Younger Patients Undergoing Total Knee Arthroplasty. Issue 2 (May 2022) - Anatone, Alex J.; Richardson, Shawn S.; Kahlenberg, Cynthia A.; Gausden, Elizabeth B.; Figgie, Mark P.; Blevins, Jason L.
Background : Younger patients are undergoing total knee arthroplasty (TKA) at increasing rates and may face multiple revisions during their lifetimes due to mechanical complications or infections. Questions/Purposes : We sought to compare the early complication rates and revision-free implant-survival rates across age groups of patients undergoing TKA, with particular focus on implant survival in younger patients. Methods : We conducted a retrospective analysis of data taken from a national insurance database on patients who underwent primary TKA from 2007 to 2015. Kaplan–Meier curve survival analysis and log rank test were performed to evaluate revision rates in 7 age groups (younger than 40, 40–49, 50–59, 60–69, 70–79, 80–89, and 90 or more years of age). Complication rates were compared to rates in the age 60 to 79 years age groups using multiple logistic regression, controlling for baseline demographics and comorbidities. Results : There were 114, 698 patients included in the analysis. Patients in the younger than 40 years, 40 to 49 years, and 50 to 59 years age groups had increased rates of early mechanical complications; 90-day readmission rates were significantly higher in those age groups as well. Revision-free implant survival at 5 years was significantly worse in patients younger than 60 years of age, particularly those less than 40 years, who had a 77% revision-free implant-survival rate at 5 years. Conclusions : Younger patients had a higher risk of early revision after TKA, as well as an increased rate of mechanical complications and readmissions at 90 days. These outcomes suggest more study is needed to better understand these discrepancies and to better guide preoperative counseling for young patients considering TKA.